2002
DOI: 10.1002/1439-7633(20020402)3:4<274::aid-cbic274>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Watson and Crick: DNA Methylation and Molecular Enzymology of DNA Methyltransferases

Abstract: DNA methyltransferases catalyze the transfer of a methyl group from S-adenosyl-L-methionine to cytosine or adenine bases in DNA. These enzymes challenge the Watson/Crick dogma in two instances: 1) They attach inheritable information to the DNA that is not encoded in the nucleotide sequence. This so-called epigenetic information has many important biological functions. In prokaryotes, DNA methylation is used to coordinate DNA replication and the cell cycle, to direct postreplicative mismatch repair, and to dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
346
2
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 548 publications
(380 citation statements)
references
References 271 publications
5
346
2
8
Order By: Relevance
“…70 When this modification occurs in promoter regions, gene expression is altered; 71 increased methylation is associated with gene silencing or reduced gene expression. 70 In cholinedeficient cells in culture, methylation of the cyclindependent kinase inhibitor 3 gene promoter is decreased, resulting in overexpression of this gene, which inhibits cell proliferation. 72 We replicated this observation in brains of fetuses from choline-deficient mothers and found that cyclin-dependent kinase inhibitor 3 was hypomethylated and overexpressed in the neuroepithelium of the fetal hippocampus (submitted for publication); we suggest that this is the likely molecular mechanism for decreased stem cell proliferation in brains of these fetuses.…”
Section: Possible Mechanisms For the Effects Of Choline On Neural Tubmentioning
confidence: 99%
“…70 When this modification occurs in promoter regions, gene expression is altered; 71 increased methylation is associated with gene silencing or reduced gene expression. 70 In cholinedeficient cells in culture, methylation of the cyclindependent kinase inhibitor 3 gene promoter is decreased, resulting in overexpression of this gene, which inhibits cell proliferation. 72 We replicated this observation in brains of fetuses from choline-deficient mothers and found that cyclin-dependent kinase inhibitor 3 was hypomethylated and overexpressed in the neuroepithelium of the fetal hippocampus (submitted for publication); we suggest that this is the likely molecular mechanism for decreased stem cell proliferation in brains of these fetuses.…”
Section: Possible Mechanisms For the Effects Of Choline On Neural Tubmentioning
confidence: 99%
“…Prokaryotes contain DNA with N 6 -methyladenine, 5-methylcytosine, and N 4 -methylcytosine because of the presence of adenine-and cytosine-DNA methyltransferases [21]. In contrast, adenine-methyltransferases have not been described in higher eukaryotes, in which only cytosine-C5 methylation has been found.…”
Section: Bacterial Dna Obtained From An E Coli Damdcm -Strain Retainmentioning
confidence: 99%
“…In contrast, adenine-methyltransferases have not been described in higher eukaryotes, in which only cytosine-C5 methylation has been found. Moreover, cytosine methylation in mammals mainly occurs at CG sequences [21]. To determine whether content of adenine methylation or cytosine methylation other than CG methylation in bacterial DNA may account for its stimulatory capacity, we used bacterial DNA isolated from an E. coli strain deficient in both adenine and cytosine methyltransferases (E. coli SCS110 strain Dam -Dcm -).…”
Section: Bacterial Dna Obtained From An E Coli Damdcm -Strain Retainmentioning
confidence: 99%
“…1). Like in all other structures of DNA MTases with substrate DNA [4][5][6][7] and initially discovered with M.HhaI [8], the target Cyt is rotated out of the DNA helix and bound to a pocket in the protein, which presents the active site residues conserved among DNA-(cytosine C5)-methyltransferases [4,7]. Unexpectedly, in the Dnmt1-DNA structure the orphan Gua residue from the non-target strand forms a base pair with a Gua from a Gua:Cyt base pair 5 0 of the CpG site.…”
Section: Introductionmentioning
confidence: 97%